PSYCHO-SOCIAL FACTORS AS DETERMINANTS OF CULTIC INTENTION AMONG PUBLIC UNIVERSITY STUDENTS IN SOUTHWESTERN, NIGERIA (2016)
The increasing incidence of cultic behaviour (violence, murder, alcoholism, drug abuse and dispute) among university students in southwestern Nigeria has become a serious concern to parents, guardians, educators, management of tertiary institutions and government. The menace of cultism remains indelible in the minds of the victims and members of the society. Literature mostly considered cult members with little consideration for undergraduates with cultic intention (CI). This study, therefore, investigated self-concept, self-efficacy, aggression, anger, drug abuse, parental and peer influence on CI among university students in southwestern Nigeria, The study was anchored on social learning and cultism theories while the descriptive design of the ex-postfacto type was adopted. Multi-stage sampling procedure was used. First, purposive sampling technique was used to select all the federal and state universities in southwestern states of Nigeria. The private universities were excluded because many of them were faith-based and were strictly administered with little freedom of expression for the students. With the assistance of the students’ affairs offices in the universities, Cultic Behaviour Manifestation Scale (CBMS) was administered to 500 students in each university to screen out those without cultic intention. At the third stage, universities with at least 50.0% cultic intention rating were purposively selected. These are: Obafemi Awolowo, Ile-Ife, University of Ibadan, Federal University of Agriculture, Abeokuta, Olabisi Onabanjo Ago-Iwoye, Lagos State University and Ekiti State University. At the fourth stage, proportionate sampling technique was used to select 200 undergraduates with cultic intention across the faculties in each of the six universities. The participants were 76.2% males with 23.8% females. An administrative officer of the students’ affairs division in each university was purposively selected for key informant interview. In-depth interviews were also conducted with the Presidents of the students’ union in the universities. Drug abuse (r=0.91); aggression (r=0.87); self-concept (r=0.87); self-esteem (r=0.85); self-efficacy (r=0.82); anger (r=0.82); parental influence (r=0.77); peer influence (r=0.76); and cultic intention (r=0.73) scales were used for data collection. Data were analysed using Pearson product moment correlation and Multiple regression at 0.05 level of significance, while qualitative data were content analysed. Parental influence (r=0.68), aggression (r=0.52), peer influence (r=0.44), anger (r=0.40), self-esteem (r=0.37), drug abuse (0.27), self-efficacy (r=0.24) had significant relationship with CI while self-concept did not. Self-concept, self-esteem, drug abuse, anger, aggression, parental influence and peer influence jointly determined CI and accounted for 42.2% of its variance (F(5,82.01); R2=0.42). Parental influence (β=0.49), aggression (β=0.11), peer influence (β=0.06), self-concept (β=0.04) and self-esteem (β=0.02) had relative contributions on CI while, self-efficacy, anger and drug abuse did not. The students’ union leaders and university administrative staff posited that perceived social injustice, parental influence, peer influence and poor mentoring were critical factors for students’ involvement in cultic activities in universities in southwestern Nigeria. Low self-concept, self-esteem, aggression, parental influence and peer-influence precipitated cultic behaviour among university students in southwestern Nigeria. Counselling psychologists and educational administrators should take cognisance of these variables while managing university students with cultic behaviour. Keywords: Cultic intention, Aggression, Parental influence, Self-concept, University students in southwestern Nigeria Word count: 484